Handbook of recycling : state-of-the-art for practitioners, analysts, and scientists - Worrell, Ernst; Reuter, M. A. (Elsevier, 2014)
Handbook of Recycling is an authoritative review of the current state-of-the-art of recycling, reuse and reclamation processes commonly implemented today and how they interact with one another. The book addresses several material flows, including iron, steel, aluminum and other metals, pulp and paper, plastics, glass, construction materials, industrial by-products, and more. It also details various recycling technologies as well as recovery and collection techniques. To completely round out the picture of recycling, the book considers policy and economic implications, including the impact of recycling on energy use, sustainable development, and the environment. With contemporary recycling literature scattered across disparate, unconnected articles, this book is a crucial aid to students and researchers in a range of disciplines, from materials and environmental science to public policy studies.- Resumé vydavatel
Keywords: recyklace odpadu; druhotné suroviny; ochrana životního prostředí; waste recycling; secondary raw materials; environmental protection; elektronické knihy; příručky; sborníky; electronic books; papers of several authors; handbooks and manuals